Diagnostic Methods of the Company's Creditworthiness - Koliesnichenko, Anastasiia; WU, Linfeng (Хмельницький національний університет, 2024)
To conduct an analysis of the company's creditworthiness, it is necessary to study the analyzed business from different points of view. It should be noted that the main elements of the study are related to liquidity ratios, debt ratios, activity ratios, profitability ratios, and economic efficiency ratios. These aspects are very informative and extremely important. Despite the availability of various methods, there are no methods that would obtain completely objective results. Because each of them is based on different approaches, which are not perfect. As a result, these methods do not take into account all aspects related to creditworthiness. That is, the shortcomings of existing methods require constant updating in practice.
Keywords: diagnostics; creditworthiness; business; analysis